Faciliting Communication between Engineers with CARES - Guzzi, Anja; Begel, Andrew and (Proceedings of the International Conference on Software Engineering, 2012)
When software developers need to exchange information or coordinate work with colleagues on other teams, they are often faced with the challenge of finding the right person to communicate with. In this paper, we present our tool, called CARES (Colleagues and Relevant Engineers' Support), which is an integrated development environment-based (IDE) tool that enables engineers to easily discover and communicate with the people who have contributed to the source code. CARES has been deployed to 30 professional developers, and we interviewed 8 of them after 3 weeks of evaluation. They reported that CARES helped them to more quickly find, choose, and initiate contact with the most relevant and expedient person who could address their needs.